Ethical and legal issues in end-of-life care: the case of life prolongation - Macedo, João Carlos Gama Martins (2022)
This article aims to make an ethical and legal reflection on end-of-life care, specifically on life- prolongation resulting from technical and diagnostic investment in current health care. This practice called dysthanasia, which in practice is also known as therapeutic obstinacy or futility in care - which is still present in health care - is well described and censored in the deontological codes of doctors and nurses and legal texts (specifically in Portugal). However, despite these documents and the national and international guidelines that contribute to preventing this phenomenon, we conclude that in parallel we need to promote death education - especially end-of-life bioethical issues -, for health professionals in particular, and society in general. The awareness of this issue, through education, will contribute to the empowerment of citizens, more humanization of health care, and, above all, a way to prevent the acts of prolonging the dying process.